2021
DOI: 10.1111/cas.15240
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐inducible lncRNA MIR210HG interacting with OCT1 is involved in glioblastoma multiforme malignancy

Abstract: An insufficient oxygen supply within the intratumoral environment, also known as hypoxia, induces glioblastoma multiforme (GBM) invasion, stemness, and temozolomide (TMZ) drug resistance. Long noncoding (lnc)RNAs have been reported to be involved in hypoxia and GBM progression. However, their roles in hypoxic GBM malignancy are still unclear. We investigated the mechanisms of hypoxia-mediated lncRNAs in regulating GBM processes. Using The Cancer Genome Atlas (TCGA) and data mining, hypoxia-correlated lncRNAs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Previous studies indicated that hypoxia can regulated a series oncogenes (Liu et al, 2020) or non-coding RNAs (Ho et al, 2022) to induce TMZ-resistance of glioma. In the current study, we demonstrated that SHOX2 was increased TMZresistance glioma cells, while hypoxia can induced the elevation of SHOX2 in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that hypoxia can regulated a series oncogenes (Liu et al, 2020) or non-coding RNAs (Ho et al, 2022) to induce TMZ-resistance of glioma. In the current study, we demonstrated that SHOX2 was increased TMZresistance glioma cells, while hypoxia can induced the elevation of SHOX2 in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are pieces of evidence that lncRNAs play an essential part in cancer ( Ho et al, 2022 ; Liang et al, 2022 ; Zhang et al, 2022 ). SNAI3-AS1 , an m 7 G prognosis-associated lncRNA, is an important tumor modifier in hepatocellular carcinoma tumor progression ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is recently reported that, downregulation of lncRNA plasmacytoma variant translocation 1 (PVT1) increased sensitivity of BC sells to doxorubicin (ADM), suppressed ADM-resistant BC cell proliferation and invasion, and promoted apoptosis, while PVT1 overexpression promoted ADM-sensitive BC cell growth and their resistance to ADM 97 , and the potential mechanisms that mediate the alteration could be related with the elevated MDM2 expression and AURKB-mediated p53 ubiquitination 97 . Studies showed that some of the lncRNAs could interact with transcription factors, for example, lncRNA MIR210HG, locating in nuclear regions, could interact with octamer transcription factor 1 (OCT1) 111 .…”
Section: Mechanisms For Regulation Of the Mdr-associated Factors Or S...mentioning
confidence: 99%